Determinants of Public Interest in Telemedicine Use with UTAUT and Social Cognitive Model Approaches - Meisari, Winda Azmi; Widyaningrum, Nannyk; Muhlizardy, Muhlizardy; Tri Utami, Retno; Aulia, Salma Nur (Jurnal Ilmiah Kesehatan (JIKA), 2025)
The current lack of public knowledge regarding telemedicine correlates with its low utilization as a remote health service. This is supported by Central Statistics Agency survey data, which indicates that 58,2% of subjects are unaware of telemedicine, compared to only 41,8% who are familiar with it. This research intended to analyze the determinants of public interest in utilizing telemedicine, employing the Unified Theory of Acceptance and Use of Technology or UTAUT model, and also social cognitive theory. Quantitative methodology was used, with data collected through a survey of subjects familiar with or using telemedicine. Structural Equation Modeling (SEM) was employed to investigate the correlation among many variables by assessing both the direct and indirect influences of exogenous variables on endogenous ones. The study was conducted in 2024, involving a total of 215 subjects from various regions, specifically Surakarta, Yogyakarta, and Kalimantan. The study revealed that social influence, self-efficacy, and performance expectancy were significant predictors of individuals' interest in adopting telemedicine. Conversely, effort expectancy, gender, age, and moderating variables did not show a significant effect. This study concludes that strategies focused on increasing self-efficacy, performance expectancy, and social influence need to be optimized to encourage wider adoption of telemedicine services in the community.